Standard criteria for writing a calendar study as a randomized controlled study - El Sheikou, Hawker Omran; Ghanem, Naif Ali; Hassan, Hazem (Journal of medical and pharmaceutical sciences, 2018)
Randomized controlled trials (RCTs) are an integral part of evidence- based medicine. Randomized controlled trials are the gold standard for evaluating the impact and safety of interventions, in order for the RCT to be more interactive a list of 25 items called the Standard consolidated of reporting trials (CONSORT) is used to provide a guide for researchers to make the study more accurate and transparent. The aim of this article is to: 1. Provide some information about randomized controlled trials, 2. Provide information on the guidelines in writing the randomized controlled trials by (CONSORT), 3- Facilitate the evaluation and writing of randomized controlled trials Conclusion: The article contains details and explanations of 11 of the 25 items including (Title- Summary- Methods- Randomization- Blinding), The purpose of introducing (CONSORT) is to improve the quality of the RCT experience, so that the authors are guided in writing their studies so that the study is clear, complete and transparent according to the Standard consolidated of reporting randomized controlled trials